Numerical Study of Solute Transport in Heterogeneous Beach Aquifers Subjected to Tides. Issue 3 (10th March 2020) - Geng, Xiaolong; Boufadel, Michel C.; Rajaram, Harihar; Cui, Fangda; Lee, Kenneth; An, Chunjiang
Abstract: A numerical study, based on a variably saturated groundwater flow model within a Monto Carlo framework, was conducted to investigate flow and solute transport in a heterogeneous beach aquifer subjected to tides. The numerical simulations were conducted based on our previous tracer experiments performed in a laboratory beach. Heterogeneity is assumed to be multifractal generated using the Universal Multifractal model. Our results show that heterogeneity greatly alters temporal and spatial evolution of the tracer plume migrating in the beach. The spreading coefficient of the plume shows very dynamic response to tides; it increases as the tidally driven recirculation cell overlaps with the plume and decreases as the recirculation cell moves far from the plume with tides. Descriptive statistics suggests that heterogeneity enhances spreading of the plume in the beach in an ensemble sense along with significant spatial and temporal variation. Due to heterogeneity, high spots of the pore water velocity are formed within the recirculation cell, creating transient preferential flow paths in the beach in response to tides. Contours of the Okubo‐Weiss ( OW ) parameter show that coupling with tides, heterogeneity creates vorticity‐dominated flow regions and also expands strain‐dominated flow regions more downward, indicating complex local‐scale mixing in the beach, compared to corresponding homogeneous case. Geologic heterogeneity also alters the spatial extent of the recirculating cell and induces highly variable transit time along the recirculating flow paths. The results provide insights into effects of geologic heterogeneity on seawater‐groundwater mixing and associated solute transport processes in tidally influenced coastal aquifers. Plain Language Summary: Influences of geologic heterogeneity on groundwater flow and solute transport in tidally influenced beach aquifers have not been studied. Our results reveal that the heterogeneity represented as multifractals significantly alters the spatial and temporal evolution of the tracer plume in the beach, which has important implications for the vulnerability of coastal resources to inland‐derived pollutants. In coastal regions, effective implementations of in situ remediation often rely on subsurface delivery of chemicals (e.g., dissolved oxygen and nutrients) to the polluted zone. Our results demonstrate complex behavior of solute transport and associated mixing with surround groundwater in tidally influenced beach aquifers that are strongly impacted by geologic heterogeneity. These results highlight the importance of considering geologic heterogeneity in studies of solute transport processes in coastal aquifers. Key Points: Heterogeneous hydraulic conductivity fields alter spatiotemporal evolution of the tracer plume migrating in tidally influenced beaches Heterogeneity creates high spots of the pore water velocity within mixing zone, leading to transient preferential flow paths in the beach Heterogeneity creates vorticity‐dominated zones and expands strain‐dominated zones more downward, complexing local‐scale mixing in the beach